Optimizing the Role of the Ministry of Religious Affairs' Hisab Rukyat Team in Implementing Rukyatul Hilal - Nada Putri Rohana (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2026)
This research is based on the determination of the hijri year carried out through an isbat session conducted by the Ministry of Religion of the Republic of Indonesia. In the isbat session, it was carried out after the rukyat hisab team at the designated location points throughout Indonesia. The determination of the testimony of the rukyat hilal is an important foundation in determining the beginning of the month of Kamariah. This study examines the role of the Ministry of Religion of Padangsidimpuan City to provide concrete recommendations in its role in determining the rukyat hilal. This research is a qualitative field research. The provisional results of the study show that based on Article 52 A of Law No. 3 of 2006, it guarantees that the Ministry of Religion has the authority to carry out the rukyat hilal in the month of komariah. However, how is the coordination with related institutions, and what are the obstacles faced in its implementation. The strategic role of the Ministry of Religion of Padangsidimpuan City in determining the beginning of the hijri month scientifically and sharia, as well as the efforts that can be made to increase the effectiveness and credibility of its implementation in the future.